A retórica nas fórmulas discursivas e as mudanças no discurso do Supremo Tribunal Federal brasileiro - Butieri, Kathrine (2023)
This work is part of the research line Text and Discourse in the Oral and Written modalities, of the Post-Graduate Studies Program in Portuguese at the Pontifical Catholic University of São Paulo and has as its theme the rhetoric about the legal discourse of the Federal Supreme Court ( Brazilian STF), at a time of change in which the institution's political leadership shows a strong presence in the space of public opinion. Our research analyzes the meanings and persuasive means intended by the speakers when using the word “rhetoric” (and its related expressions) in the monocratic decisions handed down by the ministers of the STF, both in the conception of the word and in the use of argumentative strategies. To achieve these goals, we base ourselves on Aristotle (2005), Albaladejo (2020), Amossy (2017), Angenot (2012), Ferreira (2015), Mateus (2018; 2022), Meyer (2007; 2018), Perelman; Olbrechts-Tyteca (2020), Reboul (2004), Tringali (1988), to address rhetorical theory; Krieg-Planque (2010; 2002) for the theoretical and methodological framework of the notion of formula in Discourse Analysis; Bardin (2011) for methodological procedures in Content Analysis. The corpus is formed by 355 monocratic sentences and focuses on the 186 records of the repetition of the word “rhetoric” and its compounds, in the period from 2012 to 2021. For analysis, we selected six terms: mere rhetoric, circumlocution of rhetoric, empty argument of rhetoric, defensive rhetoric, rhetorical formulae, and rhetorical concern. The research carried out allowed us to observe that the six highlighted terms constitute discursive formulae and served as a persuasive resource in the speeches of the ministers of the Brazilian STF. However, the use of formulas in this context only sought to end the controversy and win the discussion in a borderline situation between rhetoric, eristics and clichés. We conclude that the circulation of these formulas with the word “rhetoric” nowadays, as analyzed in the corpus, due to its polysemy and subjectivity of use, needs to be reassessed so that an argumentative exchange between the interlocutors in equity for the solution of conflicts occurs. We also propose to consider the other positive meanings of rhetoric in the service of persuasion and dialectic and not just in the service of itself in just winning the debate with an eristic sense